Utilising YouTube to Facilitate English Speaking Skills Improvement among EFL Learners - Melisa, Melisa; Abid, Abid; Muhamad, Farid (Universitas Negeri Gorontalo, 2023)
This study aimed to explore how students utilize YouTube as a virtual platform for developing English- speaking skills. A qualitative approached was used to capture the experiences of three participants in English Department discussing how YouTube improved their English-speaking skills. To analyse data, a thematic analysis was employed. The findings revealed three major themes, namely employing self- directed learning approach, engaging with videos for active learning, and receiving diverse content exposure for language enrichment. These shed light on the many ways that YouTube helps students improve their English speaking skills and advance our understanding of how students use the platform for foreign language learning.